Optimal Control for the Trajectory Planning of Micro Airships - Blouin, Charles; Lanteigne, Eric; Gueaieb, Wail (Université d'Ottawa | University of Ottawa, 2017)
The objective of this paper is to demonstrate the application of optimal control for generating dynamically constrained minimal time trajectories in micro unmanned airships. By design, airships are generally underactuated and underpowered limiting their maneuvering capabilities. Using a simplified dynamic model derived with experimentally derived coefficients, two trajectory planning simulations are solved using optimal control. The generated trajectories are then evaluated experimentally on a micro airship to demonstrate that optimal control can be used in open loop over short distances.
Keywords: Optimal control; UAV; Trajectory planning; Mobile robots